Pengaruh Penggunaan Media Sosial Tiktok Terhadap Perkembangan Karakter Peserta Didik - Nurhayani; Nurul Khoiriah Hairani; Nurul Rizki Amalia; Siti Rubiah Dalimunthe; Munawaroh Sibagariang (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2023)
Observational evidence showing behavioral and grammatical development in low-income students was the driving force of this research. Therefore, in an effort to improve student learning outcomes, researchers carried out action studies in the classroom. The objectives of this research are as follows: (1) Identify the factors that cause students' low character development (2) Understand how the use of TikTok social media affects students' character development; (3) Understand the important role of parents in monitoring their children's media use at home. Thirty-two fifth grade students participated in this investigation. This research measures the developmental domain of students' characteristics in terms of behavior and grammar. As a result, it was found that the development of students' characteristics can change in positive or negative directions through TikTok social media, it just depends again on parenting patterns and parental supervision of these students. The qualitative method provides data based on direct answers given by students to questions. provided by researchers regarding the problems that occur. This data encourages teachers to be able to respond and provide direction and control student behavior and develop students to have good and regular grammar.